2014
DOI: 10.7863/ultra.33.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography in the Differential Diagnosis of Benign and Malignant Cervical Lesions

Abstract: Ultrasound elastography is a promising technique that is easy and rapid to perform and can help identify cervical lesions that are likely to be malignant. It is obvious that the strain ratio yielded better results than the elasticity score. Both methods are semiquantitative, but quantification of the strain ratio is finer than that of the elasticity score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
1
26
2
3
Order By: Relevance
“…In study III tumours in patients with advanced stages were more easily demarcated, had higher strain ratio and a tendency for a higher elasticity score even if it was not statistically significant compared to early stages, probably due to a small patient cohort. The max strain ratio found in tumours both early (1.87) and advanced (3.06) was lower than in previously published studies where a strain ratio of 4.5 was suggested as a cut-off between benign and malignant cervical tissue (152,181). These difference are explained by different study populations as patients with benign conditions such as cervical fibroma and dysplasia were included in the other studies, another reference tissue used for the calculation of strain ratio (parametrium) and last but not least different US equipment was applied both for examination and software for the analysis.…”
Section: Locally Advanced Stagescontrasting
confidence: 63%
“…In study III tumours in patients with advanced stages were more easily demarcated, had higher strain ratio and a tendency for a higher elasticity score even if it was not statistically significant compared to early stages, probably due to a small patient cohort. The max strain ratio found in tumours both early (1.87) and advanced (3.06) was lower than in previously published studies where a strain ratio of 4.5 was suggested as a cut-off between benign and malignant cervical tissue (152,181). These difference are explained by different study populations as patients with benign conditions such as cervical fibroma and dysplasia were included in the other studies, another reference tissue used for the calculation of strain ratio (parametrium) and last but not least different US equipment was applied both for examination and software for the analysis.…”
Section: Locally Advanced Stagescontrasting
confidence: 63%
“…In these cases, the malignant tissues are shown less compressible, resulting in less strain than the normal tissues under uniform stress. Recently, sonoelastography imaging was used to study the normal and abnormal cervix [1619]. Several studies have shown the potential of sonoelastography in monitoring and predicting the therapeutic response such as the responding and non-responding malignant tissues in patients following CCRT [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also investigated the use of elastography in differential diagnosis of uterine disorders. It has been shown that elastography may differentiate benign and malignant cervical lesions 21 . Preis et al 8 reported that normal and atrophic endometria appear softer on elastography than endometrial polyps, hypertrophy, and cancer in perimenopausal women with an endometrial thickness of greater than 5 mm 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elastography may differentiate benign and malignant cervical lesions. 21 Preis et al 8 reported that normal and atrophic endometria appear softer on elastogra-phy than endometrial polyps, hypertrophy, and cancer in perimenopausal women with an endometrial thickness of greater than 5 mm. 8 Similar results were obtained in a very recent study, in which the authors concluded that although elastography does not differentiate endometrial hyperplasia and endometrial polyps, it can distinguish pathologic endometrial changes from a normal endometrium in patients presenting with a sonographic finding of a thickened endometrium.…”
Section: Discussionmentioning
confidence: 99%